Predicting firefighting simulation tasks performance from firefighters' specific fitness tests. - Lin, Yu-Wei; Hsu, Yu-Chuan; Su, Ming-Jen; Wu, Bo-Han (Work, 2025)
Background: Previous studies have examined the correlation between fitness characteristics and firefighter's job performance. Objective: This study was to examine the ability of firefighters' specific fitness tests to predict firefighter's job performance. Methods: Fifty fire academy trainees (48 males and 2 females, age = 27.3 ± 3.8) participated in the firefighting simulation tasks and firefighters' specific fitness tests (which included standing long jump, backward overhead medicine ball throw, 6-meter shuttle run, trap bar deadlift, leg tuck, farmer's walk, 1500-meter run). Participants wore personal protective equipment (PPE) and self-contained breathing apparatus (SCBA) to complete firefighting simulation tasks (which included 12 structural firefighting tasks). Pearson's correlation analysis and multiple stepwise regression analyses were performed. Results: The results demonstrated that standing long jump (r = −0.290, p < 0.05), backward overhead medicine ball throw (r = −0.657, p < 0.05), 6-meter shuttle run (r = −0.318, p < 0.05), trap bar deadlift (r = −0.760, p < 0.05), leg tuck (r = −0.392, p < 0.05), farmer's walk (r = 0.701, p < 0.05), and 1500-meter run (r = 0.536, p < 0.05) were significantly correlated with the firefighting simulation tasks. In addition, the multiple regression models identified that 78.8% of the variance in performing the firefighting simulation tasks were related to 1500-meter run, trap bar deadlift, farmer's walk, and backward overhead medicine ball throw. Conclusions: Measures of strength, load-carriage capacity, power and aerobic capacity best predict firefighting simulation tasks performance. Regular assessment and maintenance of these specific fitness levels enhances work capacity within firefighting.